Comparison of sprayability and solubility of bio-based lubricants with liquid carbon dioxide - Meier, Trixi; Gross, Daniel; Hanenkamp, Nico (MM Science Journal, 2021)
In recent years, cryogenic minimum quantity lubrication (CMQL) has been established in comparison to pure cryogenic cooling. The used oil has a crucial influence on the success of the technology. The aim of this study is to investigate the influence of oils from renewable resources with regard to their miscibility with carbon dioxide (CO2) and their spraying behavior. Ten different bio-based oils (synthetic ester, natural ester and fatty alcohol) have been examined regarding their suitability for CMQL compared to a conventional mineral hydrocrack oil. A validation based on sprayability and solubility properties with liquid CO2 has been performed. The sprayability and the resulting oil droplet size have an impact on the amount of oil entering the process zone and thus on the lubrication performance of the coolant concept. For this reason, a high-speed camera has been used to capture shadow images of the jet from an external cooling nozzle. In addition the width, intensity and uniformity of the oil application were evaluated. The solubility of the bio-based oils in CO2 is investigated in a static mixing chamber with varied mixing ratio. The miscibility of the bio-based oils in a single channel supply system was investigated with high-speed recordings of a dynamic mixing chamber. The results of the various experimental setups have been compared.<br
Keywords: CMQL; milling; turning; bio-based oils; carbon dioxide